Multiaspective diagnostics of training loads as well as biomechanical parameters and blood indices among leadingelite race walkers preparing for participation in the Olympics - Mleczko, E.; Mirek, W.; Dabrowski, Z.; Fraczek, B.; Forczek-Karkosz, W.; Sudol, G.; Gradek, J. (Journal of Kinesiology and Exercise Sciences, 2019)
Research problem: In the narrative review in the introductory chapter of this study, it was shown that there are no scientific methods or tools for researching the Functional Overreaching (FOR) state limit, which determines the occurrence of the phenomenon of Non-functional Overreaching (NFOR) and the overtraining syndrome - OTS. Research objective: In principle, this research was conducted to provide evidence of the possibility of developing, implementing and controlling such a programme for preparation to participate in the Olympic Games of champions among athletes in race walking, which will guarantee that the applied training load does not cause a state of non-functional overload. Material and methods: Six walkers took part in the research, presenting the level of the international and national master class at 20 and 50 km. They were all medallists of the Polish championship. Three of them have already participated in the Olympic Games, one was a medallist at the European and World Championships. In selected periods of the developed annual training plan, measurements in variability of walking speed at the level of the anaerobic threshold (starting speed) were carried out using the pitch test. The observation of the sports training process was supplemented with a multifaceted observation of the effects of overreaching training (ORT), which included the following measurements: 1. somatic features and anthropometric indices; 2. haematological parameters of the blood and non-enzymatic antioxidant factor, glutathione (GSH), vitamin D3, and blood serum concentrations: pro-inflammatory cytokines -IL1ß and IL-6, markers of oxidative stress, TAC, alpha- and gamma-TOC, proteins: Aponectin and Zonulin; 3. electromyographic (EMG) recording in the field and laboratory conditions and the work of the lower-limb muscles during the gait test with a gradual increase in its speed. Systematic monitoring of the nutritional status of walkers throughout the training cycle was performed and, on this basis, the following were established: a) principles of a rational diet and individual nutritional recommendations; b) dietary recommendations during the period of training and biological regeneration; c) individual strategies of dietary supplementation aimed at supporting immunity. Research results: Results of research have been presented in each segment of the study. Using the system-functional discourse method, they are discussed, interpreted and justified to assess the induction of beneficial skeletal muscle adaptation, ranging from increased endurance due to mitochondrial biogenesis and angiogenesis, to increased strength due to myocyte hypertrophy. Frequently encountered forms of application were: narration, description and argumentation. Conclusions: 1) The developed model of sports training for race walkers, as well as the proposed system of control and monitoring adaptation processes to physical effort can be considered as a reference point for development, for top sports class competitors, safe preparation for the target event (not exceeding the functional load limit); 2) The qualification of one of its participants for the Olympic team and the winning of medals at the Polish Championships by the remaining competitors should be considered a measurable effect of the performed observation.